Screening characteristics of PSEN1 E280A mutation carriers and non-carriers in the API Autosomal Dominant Alzheimer¿s Disease Colombia Trial (2020)
ABSTRACT: Background: The Colombia Alzheimer’s Prevention Initiative (API) Registry was aresource for enrollment into the API Colombia clinical trial. Potentially eligible can-didates from the Colombia API Registry went through a prescreening and then in-person screening process with the goal of enrolling them in the API ADAD ColombiaTrial. Analysis of screening data might provide additional information to consider forother AD prevention trials. We present descriptive screening data from the API ADADColombia trial in Presenilin 1 (PSEN1) E280A mutation carriers vs non-carriers.Method: Consent was obtained from 319 potentially eligible participants after pre-screening. Screening data from 315, including 210 mutation carriers, were used tocompare demographics, medical comorbidities, toxic and reproductive antecedents,selected clinical, functional, and anthropometric measurements, vital signs, and brainMRI and laboratory results in the mutation carrier and non-carrier groups. Descriptivestatistics comparing mutation carriers and non-carriers were performed using gener-alized linear regression models using link function according to whether the outcomewas categorical or numerical. Results were adjusted for age, sex, level of education,depression or body mass index (BMI) depending upon which measurements were com-pared.